Perbandingan Penyisihan COD Dari Limbah Cair Produksi Minyak Sawit Menggunakan Bakteri Kultur Tercampur Dan Kultur Tunggal - Putri, Gustriana; Andrio, David; Amraini, Said Zul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm oil mill effluent (POME) has a COD content of 44,444 mg / L. The use of mixed cultures and single cultures such as Saccharomyces cerevisiae in removing Chemical Oxygen Demand (COD) has the advantage of being able to adapt to mixed substrates. This research aims to study the comparison of COD removal from POME using mixed culture bacteria and single culture. This study was conducted in a batch system using Circulating bed reactor (CBR) with a working volume of 20L and 5L, the ratio of inoculum: substrate = 30%: 70%. The results showed that the efficiency of dissolved COD removal in mixed cultures was proportional to a single culture that was equal to 42% with a removal rate of 1.114 mg / L / day. Meanwhile, the growth rate of VSS in mixed culture bacteria was 2.800 mg / L / day and a single culture was 2.667 mg / L / day.Key words: Palm oil mill effluent, mixed culture bacteria, single cultures, COD Removal, VSS